Transmural migration of a subcutaneous ureteral bypass into the intestine in three cats. (14th April 2022) - Boullenger, J.; Lafuma, F.; Baudin Trehiou, C.; Blond, L.; Gibert, S.; Kulendra, N.
Abstract : Subcutaneous ureteral bypass™ is a device placed in cats with ureteral obstruction. The most common complications include system occlusion, urinary tract infection and sterile cystitis. In this case series, we describe three cats with subcutaneous ureteral bypass devices placed where transmural migration of subcutaneous ureteral bypass catheters into the small intestine resulted in gastrointestinal signs, urinary infection and subcutaneous ureteral bypass occlusion. The system was changed in one case and removed in the other two. In all cases, an intestinal resection and anastomosis was performed. All cats had a good medium‐term outcome, and urinary infection persisted in the case for which the subcutaneous ureteral bypass system was changed. Transmural migration of the device should be ​considered in cats with subcutaneous ureteral bypass presenting with persistent urinary tract infection, gastrointestinal signs or device obstruction, even if imaging studies such as ultrasound or contrast studies do not demonstrate any abnormalities.